2001
DOI: 10.1007/s004320100249
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal squamous cell carcinomas with DNA replication errors (RER + ) are associated with p16/pRb loss and wild-type p53

Abstract: The present study demonstrates the probable role of MSI in esophageal squamous cell carcinoma in the Indian population. Instability associated with the repetitive sequences--the revealing marks of loss of DNA replication fidelity may serve as an indicator of predisposition to esophageal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…To the best of our knowledge, there is no published data on LOH or MSI at the RBL2/p130 gene locus in retinoblastoma although LOH in the 16q12 region was demonstrated in other neoplasms like multiple myeloma, hepatocellular carcinoma and esophageal squamous cell carcinoma. [12][13][14][15] Besides these, gross allelic loss detected by comparative genomic hybridization and other cytogenetics studies were shown at this chromosomal region in neuroblastoma, and hepatocellular, prostate and breast carcinomas. 16,17 Our results show that 57.9% of the informative retinoblastoma tumors have allelic loss within the RBL2/130 gene.…”
Section: Discussionmentioning
confidence: 85%
“…To the best of our knowledge, there is no published data on LOH or MSI at the RBL2/p130 gene locus in retinoblastoma although LOH in the 16q12 region was demonstrated in other neoplasms like multiple myeloma, hepatocellular carcinoma and esophageal squamous cell carcinoma. [12][13][14][15] Besides these, gross allelic loss detected by comparative genomic hybridization and other cytogenetics studies were shown at this chromosomal region in neuroblastoma, and hepatocellular, prostate and breast carcinomas. 16,17 Our results show that 57.9% of the informative retinoblastoma tumors have allelic loss within the RBL2/130 gene.…”
Section: Discussionmentioning
confidence: 85%
“…That study was carried out at seven microsatellite markers in the 2p, 3p, and 16q loci in a cohort of patients from the Indian population. 24 Thus, there are large discrepancies in the findings from these studies, probably as a result of the different technologies used in the various studies, the number of cases and microsatellite markers investigated, and also the specific microsatellite markers used in the studies. Another important factor that cannot be ignored is the fact that these findings are a true reflection of the population genetics of the population group being investigated.…”
Section: Discussionmentioning
confidence: 98%
“…MLH1 promoter hypermethylation has been suggested to be the main cause of MLH1 silencing, leading to microsatellite instability (MSI). In ESCC, MSI is observed in 8-59 % of tumors [58][59][60][61][62][63][64][65]. Loss of the MLH1 protein was found in 72 % of ESCC tumors, concordant with MLH1 promoter hypermethylation [66].…”
Section: Alterations In Dna Methylation In Esccmentioning
confidence: 98%